Stock Prices Affected by Debt to Equity Ratio and Net Profit Margin in Pharmaceutical Sub-Sector Companies Listed on The Indonesia Stock Exchange (IDX) For the 2019-2020 Period - Sanusi Silitonga, Eddy (Dinasti Publisher, 2021)
The purpose of this research is to determine the effect of debt to equity ratio and net profit margin on the stock price of Pharmaceutical companies on the Indonesia Stock Exchange. The type of approach in this research is quantitative—the type of analysis using associative analysis with the classical assumption method, model testing, and hypothesis testing. Simultaneous research results affect stock prices. Partially debt to equity ratio and net profit margin affect stock prices. The coefficient of standardization of the most significant beta is the variable net profit margin, so it can be concluded that the most influential variable is the variable net profit margin.